2013
DOI: 10.1007/s00114-013-1078-6
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopic documentation of Oligocene bladder stone

Abstract: Discovery of a fossil (30-35 million-year-old) urolith from Early Oligocene deposits in northeastern Colorado provides the earliest evidence for the antiquity of bladder stones. These are spherical objects with a layered phosphatic structure and a hollow center. Each layer is composed of parallel crystals oriented perpendicular to the surface. Macroscopic and microscopic examination and X-ray diffraction analysis, along with comparison with 1,000 contemporary uroliths, were used as evidence in the confirmation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Histologic section (destructive analysis) of such concretions (whether biologically or geologically-derived) may identify features that distinguish among them (Biehler-Gomez et al, 2019a), but not always. Sophisticated studies (e.g., Raman spectroscopy) may be required to even prove that they are biologically derived (Marshall et al, 2006(Marshall et al, , 2010Rothschild et al, 2013;Thomas et al, 2007). The potential value offered by analysis of concretions supports their collection and analysis.…”
Section: Physiologic Alterations Produced By Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Histologic section (destructive analysis) of such concretions (whether biologically or geologically-derived) may identify features that distinguish among them (Biehler-Gomez et al, 2019a), but not always. Sophisticated studies (e.g., Raman spectroscopy) may be required to even prove that they are biologically derived (Marshall et al, 2006(Marshall et al, , 2010Rothschild et al, 2013;Thomas et al, 2007). The potential value offered by analysis of concretions supports their collection and analysis.…”
Section: Physiologic Alterations Produced By Diseasementioning
confidence: 99%
“…Preliminary study of uroliths and bezoars at the Armed Forces Institute of Pathology Museum (formerly part of the Walter Reed Medical Center) revealed that some uroliths had a unique mammary appearance, but most were macroscopically difficult to distinguish from bezoars (Rothschild et al, 2013). The large sample (approximately 1,000 uroliths) illustrated the breadth of appearances, but was unable to provide diagnostic criteria to distinguish among the various types.…”
Section: Urolithsmentioning
confidence: 99%
See 1 more Smart Citation